Preliminary report on the Auchenorrhyncha (Hemiptera) fauna of Kazdagi National Park with two new records for Turkey - Demir, Emine (Acta entomologica slovenica (Ljubljana), 2006)
Auchenorrhyncha specimens collected in the years 2004 and 2005 in the Kazdagi (Ida Mountain) National Park in north-west Turkey were examined. 40 species belonging to 9 families were found: 1 species belongs to the family Cixidae, 2 to Delphacidae, 2 to Tettigometridae, 1 to Meenoplidae, 3 to Issidae, 1 to Flatidae, 7 to Cercopidae, 2 to Membracidae, and 21 species to Cicadellidae. Distribution of these species in Turkey and their host plants are given along with their locality records. 31 species records are new to Balikesir, and Bubastia (s.str.) ludviki Dlabola, 1979 and Iassus mirabilis Orosz, 1979 are new records for Turkish fauna.
Keywords: entomologija; favna; narodni parki; Turčija; Turkey